Avaliação do tempo de consolidação de argamassas colantes através de métodos reológicos - Oliveira, Marcelo de Jesus Dias de (2015)
The consolidation time is the time available for the application of adhesive mortar on the substrate. The NBR 14081-1 does not specify a method of test to determining the consolidation time, however, the standard of enforcement procedures of covering floors and walls with ceramic tiles (NBR 13755 and NBR 13754) establish 2 h and 30 min as the minimum time. By considering the significant differences between the formulations, the presence of polymeric additives, besides the evolution of cement and additions, a study about how and when the consolidation of adhesive mortar happens is needed. Then, it was looked for to evaluate and determine the time of consolidation of adhesive mortars of the types ACI, ACII and ACIII by Squeeze flow and Pull out flow tests in different time intervals (30, 60, 120, 180, 240 and 300 min) in fresh state. The test methods shown to be sensitive for the determination of consolidation time of adhesive mortars, indicating the increase of the viscosity and of the adhesion of the mortar over time. For mortars in which the consolidation occurred during the time period studied, this time made up to 180 minutes after mixing. From this period the adhesive mortars suffered losses in their rheological characteristics, which would cause difficulties in the settlement stages of ceramic plates and later problems in its performance and durability. On the other hand, the tensile bond strength tests showed great variability imparing a correlation with the rheological tests.